Ambivalent colonal relations in Octavia Butler's Wild Seed - Al Ogaili, Thamer Amer Jubouri; Babaee, Ruzbeh (M. Cüneyt Birkök, Sakarya University, Turkey, 2016)
This article explores postcolonial powers of ambivalence in Octavia Butler’s Wild Seed (1980). It will offer an in-depth analysis of the thematic and ideological characteristics of selected work. We will mainly focus on the theme of the mutual relationship between the colonized and the colonizer in the novel. This relationship is specified to the concept of ambivalence that incarnates the dual, yet, uncontrolled relationship between the colonized and the colonizer. Nevertheless, the colonized considers the colonizer as oppressive but an envious power; and the colonizer judges the colonized as inferior but indigenous. The colonial relationship will also be revealed by using the concept of self-other. Such concept scrutinizes the way the colonized and the colonizer perceive and resist each other. Thus, the study’s main focus point is the power relationship developed in the light of colonial ambivalence and self-other continuum. The colonial characteristics of this study offer a new interpretation of the colonial relationship depicted in the novel. Accordingly, the ambivalent relationship between the colonized and the colonizer will be equal (i.e. both of them have positive and negative attributes). This interpretation paves the way for other discourse studies interested in the depiction of the colonized and the colonizer relationship in postcolonial literature in general, and in Butler’s fiction in particular.